Pojavljanje lopataste govnačke Stercorarius pomarinus v Sloveniji - Rubinič, Borut; Vrezec, Al (Društvo za opazovanje in proučevanje ptic Slovenije, 2015)
The article deals with the occurrence of the Pomarine Skua Stercorarius pomarinus in Slovenia. Four observations of this species have been recorded todate, the last two being the recoveries of two cadavers. The first one was afull-grown female found on June 17th 1994 at Fiesa on the Adriatic coast, thesecond a juvenile female found on a road in the very centre of Ljubljana. Prispevek obravnava pojavljanje lopataste govnačke Stercorarius pomarinus v Sloveniji. Doslej so znana štiri opazovanja te vrste. Zadnji dve najdbi sta kadavra: 17.6.1994 je bila najdena odrasla ž. v Fiesi na Jadranski obali in 28.9.1999 mlada ž. na cesti v samem središču Ljubljane.